Using scaffolding academic literacy practices in tertiary classrooms: A South African case study - Bertram, Carol; Johnson, Kathryn; Goldring, J.P. Dean (Critical Studies in Teaching and Learning, 2023)
Academic development research supports embedding academic literacies development in disciplinary teaching. This enables students to experience reading and writing as disciplinary academic practices. However, few lecturers have the language knowledge and the pedagogical expertise to do this. The Reading to Learn pedagogy provides a scaffolded methodology that lecturers in higher education can adapt. We reflect on our own experiences of using these scaffolded academic literacy practices in three cases: with first year biology students, biochemistry Honours students and Masters in Education students. We argue that scaffolded academic literacy practices are useful because they emphasise both the reading and writing of texts in the discipline, provide an educational approach to plagiarism by modelling how to meaningfully paraphrase academic text, and support learner engagement. Additionally, the professional learning opportunities help academics to develop both knowledge of language and a clear methodology which can be adapted to a range of disciplines and levels.